Dampak Pengunjung dan Limbah Domestik Terhadap Kualitas Air Serta Ekosistem Ikan di Perairan Sumber Air Cirahab - Hermawan, Hermawan; Haerani, Yeni; Nuraisyah, Rina; Saudi, Saudi (Universitas Garut, 2023)
Detergent is a product that has a function as a dirt remover on clothes when washing, detergent is disposed of excessively in waters it will have a negative impact on aquatic biota, such as fish, aquatic plants, or organisms that live in water, besides that it will also reduce O2 levels in water, damage organs in fish and death in fish due to detergent pollution. The more the level of detergent pollution in the water, the more severe the death of aquatic biota will be, and vice versa, the lower the level of pollution, the better the life of aquatic biota there. Pollution is also one of the disturbers in the respiration process in the ecosystem so that the ecosystem will be disturbed by the amount of pollution from tourists and the domestic wastes they carry. This research was conducted with qualitative research using observation / observation methods and experiments on measuring the level of detergent in these waters.T he parameters seen from this study are water temperature, water pH, chemical content in water and fish in Cirahab waters. The results showed that the concentration of detergent was very high, garbage from plastic, bottles and food scraps from visitors scattered around Cirahab waters. Judging from this, the aquatic ecosystem will be disturbed and will threaten the survival of aquatic biota including fish. Fish will experience respiratory problems, namely in the gills, gills will experience damage and even mass death in the fish ecosystem in Cirahab waters. Keywords: Visitors, Domestic Waste, Fish Ecosystems